Free thyroid hormones and mortality in caucasians undergoing angiography: the Ludwigshafen Risk and Cardiovascular Health (luric) study - Merke, Anette; März, Winfried (Endocrine practice, 2017)
Objective: Alterations in thyroid hormone functions are associated with mortality and morbidity. Data on euthyroid individuals are very limited and controversial. We therefore investigated the relationship between circulating thyroid hormones and all-cause and cardiovascular (CV) mortality in participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study and their association with morbidity. Methods: LURIC, a prospective, observational study of a hospital-based cohort of Caucasians, was recruited between June 1997 and May 2001 at the Ludwigshafen General Hospital, Ludwigshafen, Germany. Mortality was recorded for a follow-up period of 10 years. The current investigation includes 2,507 patients without overt thyroid disease who all underwent coronary angiography. Blood was drawn before angiography. We evaluated the association between thyroid hormone concentrations and mortality. Results: Low free triiodothyronine (FT3) (hazard ratio [HR], 1.00 versus 0.54; lowest versus highest quartile) and high free thyroxine (FT4) (HR, 1.52 versus 1.00; highest versus lowest quartile) were significant predictors of all-cause and CV mortality, independent of age and sex. Thyroid-stimulating hormone showed no consistent correlation with mortality. Conclusion: High FT4 and low FT3 concentrations are significantly related to all-cause and CV mortality. These findings suggest that free thyroid hormones should be measured and considered in patients at intermediate to high risk of coronary heart disease. Abbreviations: BMI = body mass index CAD = coronary artery disease CCI = Charlson Comorbidity Index CI = confidence interval CV = cardiovascular eGFR = estimated glomerular filtration rate FT3 = free triiodothyronine FT4 = free thyroxine HR = hazard ratio T3 = triiodothyronine T4 = thyroxine TSH = thyroid-stimulating hormone
Gesehen am 26.09.2018
Published: November 16, 2016